Simulasi Sebaran Penyakit Blas Pada Tanaman Padi Menggunakan Model Spatial Multi Criteria Evaluation: Studi Kasus Kabupaten Karawang dan Purwakarta - Busyairi Latiful Ashar; Ali Nurmansyah; Widodo Widodo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2019)
Dispersal Simulation of Rice Blast Disease Using Spatial Multi Criteria Evalution Model: Case Study In District of Karawang and PurwakartaRice blast is caused by Pyricularia oryzae. The potential epidemic of this disease can be spatially simulated using the MCA (Multi Criteria Analysis) method based on geographical characteristics, cultivation practices, and eviromental condition. A software that can be used for MCA is SMCE (Spatial Multi Criteria Evaluation). This study was aimed to predict the spatial dispersal of blast disease using SMCE model, and identify the factors that supports the epidemic. The study was conducted in February - August 2018 in Karawang and Purwakarta District. The research methods include observing the severity of blast disease, cultivation practices and environmental conditions, and analyzing SMCE. The SMCE analysis uses rice crop maps from the Sistem Monitoring Pertanaman Padi (Simotandi), which consists of grouping factors, standardizing factors, and weighting factors. The SMCE results are a simulation map of blast disease dispersal which is then compiled with predictions of its severity. Accuracy of prediction results was evaluated by MAPE (Mean Absolute Percentage Error) based on observational data on actual disease severity. The prediction results for Karawang and Purwakarta showed means of accuration 78.16% and 73.95% respectively. In general, factors that have a strong influence on the development of blast disease include altitude, distance from source of the epidemic, history of disease in the fields, number of spores (inoculum) trapped, irrigation quality, application of herbicides, soil nutrient (N, P, K) contents and the level of soil acidity.